PENGARUH LATIHAN IMAGERY INTERNAL DAN EKSTERNAL ERHADAP KETEPATAN PASSING LAMBUNG PEMAIN SEPAK BOLA DI SSB PUTRA BUANA - Zulkarnaen; Mujriah; Rindawan (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2024)
This study examined the effect of internal and external imagery training on the accuracy of lofted passes among football players at SSB Putra Buana. The study used a two-group pretest-posttest experimental design. From a population of 48 players, 20 players aged 13-14 years who met the attendance and training-history criteria were selected and assigned to two treatment groups. Passing accuracy was measured before and after a six-week intervention using a lofted-passing accuracy test. Data were analyzed descriptively and supported by assumption tests and t-tests. The assumption tests indicated acceptable normality and homogeneity, with all reported p-values above 0.05. Both groups improved after the intervention, but the external imagery group showed a larger increase from 62% to 80% (+18%; p = 0.01) than the internal imagery group, which improved from 60% to 70% (+10%; p = 0.05). These findings suggest that, in this sample, external imagery was more effective for improving lofted-passing accuracy. Structured imagery training can therefore be considered as a complementary method in youth football technical training.